Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Rosales Gates, Carlos Felipe (2019)
This is a strategic analysis that seeks to evaluate the different aspects to be taken into account by the organization "Fast Retailing" to define its entry into the Peruvian market; This analysis was carried out through the strategic management approach, paying special attention to the areas related to human resources and operations management.